la representación de datos como elemento informativo y de construcción de marca en las competiciones deportivas: las innovaciones tecnológicas en los grafismos de laliga Santander - Dr. José-Luis TORRES-MARTÍN,Dra. Andrea CASTRO-MARTÍNEZ,Dr. Pablo DÍAZ-MORILLA (Fonseca, Journal of Communication, 2023)
Graphics are of paramount importance in today’s sports broadcasts, as they contribute to the understanding of the event, define the visual identity of the competitions and promote the spectacularisation of these events. This study focuses on the graphic representations of data in LaLiga Santander football broadcasts. Through a bibliographic-documentary review and four in-depth interviews with LaLiga officials, the aim is to analyse the use of graphics in this competition and to describe the technical tools used to design and develop its audiovisual graphic material.